Will stability last? - William Martin; Robert Rowthorn (Center for Economic Studies and ifo Institute (CESifo), 2004)
There is no consensus about the causes of the reduction in business cycle volatility seen in many major economies over the last decade. Using stylised models of the economies of the US, Euro area, UK and Japan, we argue that economic stability has been fostered by improved monetary policy and by associated changes in the behaviour of inflation, which has itself led to a reduction in the volatility of economic shocks. Assuming an absence of cataclysmic events, our projections suggest that most major economies should continue to enjoy an unusual degree of stability.
Keywords: E3; F01; E52; 330; growth volatility; inflation; stabilisation; business cycles; US; UK; Euro area; Japan; Konjunktur; Wirtschaftswachstum; Volatilität; Geldpolitik; Inflationserwartung; Vereinigte Staaten; Grossbritannien; EU-Staaten; Japan